2004
DOI: 10.1002/bjs.4761
|View full text |Cite
|
Sign up to set email alerts
|

Survival of patients with periampullary carcinoma is predicted by lymph node 8a but not by lymph node 16b1 status

Abstract: Lymph node 8a was an independent prognostic factor in patients with periampullary malignancy, but lymph node 16b1 was not. Survival in those with metastatic lymph node 8a was not significantly different from that in patients with metastatic disease at presentation. Preoperative determination of lymph node 8a status may have important implications in selecting patients for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
2
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 56 publications
5
51
2
5
Order By: Relevance
“…The relative frequency of spread of cancer to this lymph node group has led to the advocacy of extended lymphadenectomy [28,29,30,31,32,33]. A recent study has shown that involvement of lymph node station 16 however carries no worse prognosis than involvement of more localized lymph node stations [59]. Two randomized trials have shown that although such additional lymphadenectomy does not lead to increased complications, there is no significant survival benefit [33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…The relative frequency of spread of cancer to this lymph node group has led to the advocacy of extended lymphadenectomy [28,29,30,31,32,33]. A recent study has shown that involvement of lymph node station 16 however carries no worse prognosis than involvement of more localized lymph node stations [59]. Two randomized trials have shown that although such additional lymphadenectomy does not lead to increased complications, there is no significant survival benefit [33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the characteristics of included studies. [18][19][20][21][22][23][24][25][26][27][28][29] One study was excluded due to overlap in its patient population with another study assessing additionally extraregional LNM. 29,30 No studies were excluded due to inadequate methodological quality (Supplementary Table).…”
Section: Study Selectionmentioning
confidence: 99%
“…In patients with N1-disease but without hepatic-artery LNM, median survival ranged from 16 to 21 months and 3-year survival was 23% among 60 patients in one study. 25 Estimated pooled mean survival was 15 [95%CI 12-18] months in 84 patients with hepatic-artery LNM compared to 19 [16][17][18][19][20][21][22] months in 270 patients with N1-disease without hepatic-artery LNM. Estimated pooled mean difference could be generated from 3 studies and was 3 [95%CI 0-5, p = 0.020] months.…”
Section: Hepatic-artery Lnm (Station 8a)mentioning
confidence: 99%
See 1 more Smart Citation
“…8,[30][31][32] Finally, 18 articles were included after reading the full papers (Table 1). 4,[15][16][17][18][19][33][34][35][36][37][38][39][40][41][42][43][44] …”
Section: Search Strategy and Study Identificationmentioning
confidence: 99%